SUSTAINABLE PARTNERSHIP FOR FLORICULTURE START-UP - Nyayu Lathifah Tirdasari,; Salma Mutmainah,; Idqan Fahmi, (Journal of Islamic, Social, Economics and Development, 2022)
A partnership is one of the essential aspects of business, a prominent venture, and asmall enterprise. However, creating a sustainable partnership needs many requirements and agood relationship between business and partners. These paper objectives divided into threepurposes. First, to identify the characteristics of partners. Second, to examine the existingpartnership. Third, to determine the sustainable partnership strategy. This research employedthe case study method. This study used a descriptive method by utilizing observation,interviews, and questionnaires to collect the data. This study examines a start-up in Indonesiathat focuses on providing floriculture services, such as landscape design, garden consultation,and many more. In Indonesia, the business of floriculture is experiencing a significant increase.It is evidenced by the high demand for ornamental plants, which is getting higher every year.The result indicates that the existing partnership performed less optimal in achieving theinterests of the partnership. Partners' characteristics are identified from several aspects,including gender, age, education level, gardening experience, and partnership length. Most ofthe partner who was respondents were male. From the age aspect, most partners belong to theproductive age group. This age increases work productivity in line with their physical abilities,compared to non-productive age workers. IPA analysis carried out based on two categories,namely the business and the partner. The two categories revealed different results. Thedifference perceptions considering the obstacles are due to different main objectives inimplementing each party's partnership. To fulfil the partnership improvement, having the sameviewpoint and agreement in running the partnership is necessary. This paper formulates a planfor the partnership improvement, such as to create operational standardization, to coach thepartners, to make a garden nursery, and to create an integrated operational system.